A review of Indirect Matrix Converter Topologies - Salem Rahmani; Lazhar Rmili; Kamal Al-Haddad (Renewable Energy and Sustainable Development, 2015)
<span style="line-height: 150%; font-size: 12pt; mso-ascii-font-family: 'Times New Roman'; mso-ascii-theme-font: major-bidi; mso-hansi-font-family: 'Times New Roman'; mso-hansi-theme-font: major-bidi; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: major-bidi;" lang="EN-US">Abstract<span style="line-height: 150%; font-size: 12pt; mso-ascii-font-family: 'Times New Roman'; mso-ascii-theme-font: major-bidi; mso-hansi-font-family: 'Times New Roman'; mso-hansi-theme-font: major-bidi; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: major-bidi;" lang="EN-US">—Matrix Converter (MC) is a modern direct AC/AC electrical power converter without dc-link capacitor. MC is operated in four quadrant, assuring a control of the output voltage, amplitude and frequency. The matrix converter has recently attracted significant attention among researchers and it has become increasing attractive for applications of wind energy conversion, military power supplies, induction motor drives, etc. Recently, different MC topologies have been proposed and developed which have their own advantages and disadvantages. Matrix converter can be classified as direct and indirect structures. The direct one has been elaborated in previous work. In this paper the indirect MCs are reviewed. Different characteristics of the indirect MC topologies are mentioned to show the strengths and weaknesses of such converter topologies.